Preparation, Characterization And Performance Of Tio2 Based Catalytic Pellet For Detection Of Volatile Organic Compound Under Uv Light - Juhari , Jusliha (2009)
Dewasa ini, peraturan alam sekitar ke atas sebatian organik meruap telah diketatkan di seluruh dunia